The Church Institution’s Purchase of the Foreign License for Publication of a Literary Creation in Poland - Michał Skwierczyński (Wrocławski Przegląd Teologiczny)
Canonical law does not contain detailed regulations referring to the area of contracts concluded by church institutions in domestic and international trade. The church legislator refers to the norms of the current state law in this matter. This reception also includes copyright agreements, the subject of which is a foreign entity granting a license for publishing a literary creation in Poland. This study is an attempt to present the most important issues related to this. First, the notion of the literary work on the basis of Polish and international law was approximated. Next, the need to examine the possible termination of the author’s economic rights in the country of the work’s origins was pointed out. In such a situation, the work is widely available and there is no need to conclude a license agreement. In the following part, the issue of license in the canonical order was discussed and it was shown that it comes into the area of interest in the broadly understood Church property law. The normative bases, which give the possibility to choose Polish law as the law applicable to the performance of the license agreement, were given in the article. Afterwards, the connection between the payment of royalties to a foreign entity and the collection of a flat-rate corporate, as well as withholding income tax (i.e. withheld in Poland) is made. The article ends with an analysis of the translator contract key provisions.